Accuracy Assessment of Shake Table Device on Strong Earthquake Output - Wei Guo; Ping Shao; Hai-yan Li; Yan Long; Jian-feng Mao (Advances in Civil Engineering)
In order to avoid unexpected damage of structural specimens in the test, at the beginning, a signal with small amplitude is adopted to input the shake table device to gain the transfer function and corresponding drive signal, and then a strong earthquake output can be reproduced by amplifying the drive signal proportionally. However, as there are obvious nonlinearities inherent in the shake table device and structural specimen under strong earthquakes, errors inevitably exist in the replayed and amplified earthquake output if the linear transfer function and the drive signal, which are obtained by the small amplitude input, are adopted, and the desired output signal cannot accurately be achieved. Considering this point, several typical structural experiments are introduced and analyzed in this paper to study the earthquake output accuracy of the large-scale shake table test, such as inertia and elastic specimens, large-span floor, isolated building, high-speed railway station, bridge piers, and collision of adjacent multispan bridges. The transfer function of the shake table device and structural specimen is described. The energy-time history (energy-TH) index can assess the accuracy of the shake table on the strong earthquake output in the aspect of specimens other than signals themselves. The double parameter performance table is established based on this energy-TH index. More attention should be paid to energy and amplitude for the reproduction of strong earthquakes, and the accuracy details of signal reproduction should not be too strict.